The Effect of Online Customer Rating, Online Customer Review, Free Shipping and Live Streaming on Purchasing Decisions at TikTok Shop - Salvati, Adelia; Rachmawati, Erny; Tubastuvi, Naelati; Hidayah, Arini (Asian Journal of Management Analytics, 2025)
This study aims to examine the effect of Online Customer Rating, Online Customer Review, Free Shipping and Live Streaming on purchasing decisions at TikTok Shop. This type of research uses a quantitative approach with non-probability sampling methods and purposive sampling techniques and by collecting data through questionnaires distributed online. The population in this study were students in Purwokerto. The sample obtained was 130 respondents using SPSS 25 analysis. The results showed that online customer reviews, free shipping and live streaming had a positive and significant effect on purchasing decisions. Meanwhile, online customer rating does not have a significant effect on purchasing decisions. This research contributes to business actors to optimize marketing strategies through the use of review features, free shipping and live streaming.